Intersections and Interactions in Student Experiences: Inquiry into a New Taxonomy of Experiential Learning - Green, Patrick (Experiential Learning and Teaching in Higher Education, 2024)
This piece is an invited commentary responding to the student roundtable on experiential learning (see ELTHE 7.2 Discussion Roundtable: Student Panel). Framing the essay around how students respond to experiential learning as significant learning experiences, the challenge for educators is to harness these learning experiences intentionally. Fink's integrated course design model and taxonomy of learning is introduced and remixed in this essay. Rooted in practitioner-scholar inquiry, this essay anchors practitioner research as the theoretical foundation to explore the students’ experience, emerging from experiential education practice and leading to broad inquiry focused on the learning that arises (Green, 2023). In the end, a new taxonomy of experiential learning is proposed, based on student responses to experiential learning as featured in the roundtable discussion.